A Syntactic Analysis of Sentence Patterns Made by the EFL Students of English Study Program - Kusnadi, Muhammad Fitrah; Bochari, Siska; Hastini, Hastini; Usman, Sriati (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The researcher found that students' ideas in written language are not organized structurally and adequately because of the lack of understanding of sentence patterns. Their sentences are not varied, meaningful, and effective. When the students construct a sentence, they tend to construct simple sentences consisting of subject, verb, and object. It means that they do not understand the variety of sentence patterns. This research was conducted to discover the variety of sentence patterns made by students, the most dominant sentence pattern in students' written work, and why students struggle to make sentences based on sentence patterns. This research method depends on quantitative descriptive data and statistical analysis. The population and sample of this research are the 4th-semester students of the English Education Study Program at Tadulako University. The researcher found 1.127 sentences produced by the students in their written work with seven patterns. The most dominant sentence pattern in the students’ written work is pattern SVA (subject + verb + adverb). The researcher also found that four variables make the students find difficulties in writing sentences: the students have problems in constructing affirmative and negative sentences, constructing sentences based on the rules, constructing sentence patterns because they have different understandings about sentence patterns, and because they cannot differentiate formal and informal sentences.